Basic Techniques in Biochemistry and Molecular Biology - Sharma,R K , Sangha,S P S (dreamtech Press, 2020)
Fundamentals of biochemistry and molecular biology is an important component of all disciplines of Biology. In the era of multidisciplinary approach, the basic techniques in Biochemistry and Molecular Biology are much needed by the students of Botany, Zoology, Microbiology, Biotechnology, Fisheries, Veterinary, Pharmacology, Physiology, Medicine, Genetics, Agriculture and allied subjects both at undergraduate and postgraduate levels. This book includes 15 chapters covering more than 135 experimental protocols. It discussed all the relevant topics like pH and buffers, spectrophotometry, chromatography, carbohydrates, lipids, proteins, electrophoresis, enzyme immunology, vitamins and pigments, metabolites and molecular biology. It includes a wide range of experiments from preparation of culture media to PCR, Southern and Western blotting. All the experiments have been meticulously designed and special care has been taken to the safety in laboratory and precautions are given wheresoever required.